2013
DOI: 10.1089/jwh.2012.4191
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Risk of Breast Cancer Mortality in Hispanic and Non-Hispanic White Women: The New Mexico Women's Health Study

Abstract: Obesity is reported to be associated with poorer survival in women with breast cancer, regardless of menopausal status. Our purpose was to determine if the associations of obesity with breast cancer-specific, all-cause, and non-breast cancer mortality differ between Hispanic and non-Hispanic white (NHW) women with breast cancer. Data on lifestyle and medical history were collected for incident primary breast cancer cases (298 NHW, 279 Hispanic) in the New Mexico Women's Health Study. Mortality was ascertained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…Several studies have shown that obesity is associated with increased risk of breast cancer mortality. [32][33][34][35] However, only a few studies have assessed MetS and risk of breast cancer mortality in women. 16,17 Previous studies have shown that women with MetS had an increased risk of breast cancer compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that obesity is associated with increased risk of breast cancer mortality. [32][33][34][35] However, only a few studies have assessed MetS and risk of breast cancer mortality in women. 16,17 Previous studies have shown that women with MetS had an increased risk of breast cancer compared to those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that obesity was an important prognosis factor related to an increased risk of mortality (20,21). In the Asia-Pacific region, being overweight and/or obese was significantly 1.63-fold related to the greater risk of mortality from BC.…”
Section: Discussionmentioning
confidence: 99%
“…La mediana del IMC de nuestra muestra fue 29 kg/m , valor que coincide con la literatura en la cual (42) se registra que el sobrepeso y obesidad es frecuente en pacientes con cáncer de mama . Por eso, se debe replantear al inicio de la quimioterapia una valoración nutricional para disminuir el RCV y poder (43) impactar en la sobrevida . (44) La HTA es la ECV más común y aproximadamente el 28,5% de la población es hipertensa .…”
Section: Discussionunclassified